PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) PADA MATA PELAJARAN IPAS KELAS IV SDN SUKATANI 2 KABUPATEN TANGERANG - Melyana, Angele; Mawardi; Muttaqien, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Student Team Achievement Division (STAD) cooperative learning model in the subject of Natural and Social Sciences (IPAS) for fourth-grade students at SDN Sukatani 2, Tangerang Regency. It also seeks to analyze students’ responses and identify supporting and inhibiting factors during the implementation process. The background of this research lies in the low level of student engagement in learning and suboptimal academic outcomes caused by the continued use of conventional teaching methods. This research employs a descriptive qualitative approach. The research subjects consist of the fourth-grade teacher and 25 students from the same class. Data were collected through observation, interviews, and documentation. The results show that the STAD model was implemented through well-structured planning, execution, and evaluation phases in alignment with cooperative learning principles. Students responded positively to the model, showing increased participation, confidence, and motivation to learn. Supporting factors included the teacher’s preparedness, student enthusiasm, supportive school environment, and the use of contextual learning media. Meanwhile, challenges faced included unequal participation among group members and time limitations during implementation. Based on these findings, the STAD model is effective in enhancing both the learning process and student engagement at the elementary school level.